EDUKASI PRAKTIS IBADAH DAN URBAN FARMING UNTUK ANAK USIA DINI: KOLABORASI MAHASISWA KKM UNIBA DI MADRASAH DINIYAH AL-ANAM CENDEKIA - Suhastra, Asdi; Adna, Rosalinda; Hestianti, Dwi; Sumyati, Sumyati; Mulhanah, Mulhanah; Puspa, Rani (Indonesian Collaboration Journal of Community Services (ICJCS), 2025)
The community service program conducted by KKM Group 03 students from Bina Bangsa University (UNIBA) at Madrasah Diniyah Al-Anam Cendekia aims to improve early childhood understanding of religious observances (ablution and prayer) and food security education through urban farming practices on limited land. This program uses an educational approach that is applicable, fun, and based on real-world actions. The methods implemented include simulations of ablution and prayer practices, education on the concept of urban farming, and practical farming using Styrofoam. The results of the activity indicate an increase in children's knowledge and skills in performing religious observances correctly and fostering awareness of food self-sufficiency from an early age. This program serves as a model for community service based on multidisciplinary collaboration that can be replicated in similar educational institutions